A LEXICAL ITEM IN DAYAK MA’ANYAN LANGUAGE REPRESENTING SOCIAL ENVIRONMENT: WADIAN DADAS - Fitriana Firiana; Bahing Bahing; Misrita Misrita (Program Studi Pendidikan Bahasa Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sidenreng Rappang, 2021)
Representing social environment especially in traditional dance called Wadian Dadas. The ecolinguistics study in Dayak Ma’anyan tribe: Wadian Dadas, East Barito, Central Kalimantan Province has been conducted during April 2021. The objective of the study is to analyze and compare to the present life in Indonesian culture in general. This study used descriptive qualitative method. Data collection was carried out using in-depth interview, direct observation, and literature study. The results showed that Wadian Dadas at the beginning of its appearance as a dance that functions as a ceremony that heals the sick and relieving difficulties. Because of modernity era, this dance changed the function to a preserved dance, and is categorized as a cultural dance. Which usually appears at weddings or other celebratory events. However, this is still inseparable from the mystical things contained in the dance such as the same movements, the use of clothes and paintings on the dancers' bodies that are typical of the Ma'anyan Dayak tribe.The result of this research can be used for English language learning, for example in write Descriptive Text.